Opportunistic Behaviors of Harlan Family in Knives Out (2019): Oliver E. Williamson’s Perspective - Meidina Noor Afifha; Sumayah (University of Surakarta, 2025)
(2019) through the theoretical framework of Oliver E. Williamson's concept of opportunism. The research aims to identify the indicators, manifestations, and motivations behind opportunistic actions depicted in the film. Using a qualitative descriptive method, the analysis draws from primary data in the form of scenes and dialogues, supported by secondary data from literature and theoretical reviews. The findings reveal that opportunistic behaviors in the Harlan family are driven by economic dependency, greed, and information asymmetry. Key indicators include manipulation, deceit, and exploitation of trust, as seen in Ransom's framing of Marta to nullify the will and Walt's coercion using Marta's mother's immigration status. The study demonstrates the relevance of Williamson's theory in analyzing fictional narratives, offering a unique interdisciplinary perspective. However, the research is limited to this theoretical approach and film, suggesting opportunities for future studies to explore psychological or sociological dimensions of opportunism in other works. This research highlights how cinematic storytelling can reflect complex human behaviors and ethical dilemmas.